Factors Influencing the Intention of Attending Theater Performances: Exploration Study - Sri Bramantoro Abdinagoro (The Winners, 2017)
The phenomenon of theater goers who are not satisfied when watching but at the next show they were still watching, being the opposite of the concept of satisfaction. This research aimed to find the factors that caused people to intend to watch the theater again to answer the phenomenon. The researcher used an exploratory study that focused on exploring important features in the theater performing arts on those who had been watching and who had not watched. In this study, author constructed semi-structured interview questionnaires that were focused on; (1) reason for people watching the theater, (2) theatrical attributes, (3) audience expectation, and (4) audience development. The participants of the exploratory study in this study were; (1) a group of actors and performing arts workers, (2) people who watched the performing arts, and (3) people who did not watch the performing arts. The total participants were 15 persons. From the exploration results with at least 16 keywords or phrases obtained, the researcher analyzes and classifies the keywords and phrases with the same meaning and understanding that exist in each word. There are 8 (eight) constructs formed based on these keyword groupings; theater play, theater reputation, goal achievement, theater atmosphere, satisfaction, flow, intention to watch again, and word of mouth. The results of this exploratory study at the next stage of the research will be the input of the research model.